2011
DOI: 10.1002/cpe.1913
|View full text |Cite
|
Sign up to set email alerts
|

Optimization schemes and performance evaluation of Smith–Waterman algorithm on CPU, GPU and FPGA

Abstract: With fierce competition between CPU and graphics processing unit (GPU) platforms, performance evaluation has become the focus of various sectors. In this paper, we take a well-known algorithm in the field of biosequence matching and database searching, the Smith-Waterman (S-W) algorithm as an example, and demonstrate approaches that fully exploit its performance potentials on CPU, GPU, and field-programmable gate array (FPGA) computing platforms. For CPU platforms, we perform two optimizations, single instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
18
0
2
Order By: Relevance
“…Synchronize; 14: PM s D nextPM s ; 15: end for 16: end for 17: end for 18: Reduce and Fetch the state with minimum PM s mi n from PM˛C L d CL t ,0 to PM˛C L d CL t ,63 ; 19: s D s mi n ; 20: for t L d C L t 1 to 0 do 21: j D s%2 K 2 ; 22: if t < L d then 23:…”
mentioning
confidence: 99%
“…Synchronize; 14: PM s D nextPM s ; 15: end for 16: end for 17: end for 18: Reduce and Fetch the state with minimum PM s mi n from PM˛C L d CL t ,0 to PM˛C L d CL t ,63 ; 19: s D s mi n ; 20: for t L d C L t 1 to 0 do 21: j D s%2 K 2 ; 22: if t < L d then 23:…”
mentioning
confidence: 99%
“…Zou et al [33] analyze performance and power for SW on FPGA, CPU and GPU, declaring the FPGA as the overall winner. However, they do not measure real-time power dynamically, but simplify with a static value for the whole run.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, many comparative studies indicate that Field Programmable Gate Arrays (FPGAs) can often achieve better comprehensive properties than other platforms in most cases. For example, in the work of Zou et al [9], the efficiency of the FPGA implementation of the Smith-Waterman Algorithm is 3.4× compared to the Graphics Processing Unit (GPU) and over 40× compared to the Central Processing Unit (CPU), while Kestur et al [10] demonstrated that FPGA has similar performance at higher energy efficiency compared to the CPU and GPU platforms.…”
Section: Introductionmentioning
confidence: 99%